3D printing with SketchUp : using SketchUp to generate print-ready models and transform your project from concept to reality - Dietzen, Aaron (Packt Publishing Ltd., 2023)
Working with the amazing 3D printing technology and getting access to the printing hardware is now easier than ever before. While there are many other resources that cover the general process of 3D printing, this book is the ultimate guide to creating models for 3D printing using SketchUp. You'll start with a basic understanding of how SketchUp is used in the 3D printing workflow and jump into the steps to create a print-ready model using only SketchUp. This 3D printing book will guide you in using SketchUp to modify existing 3D files and cover additional tools that make SketchUp an even more powerful modeling tool. As you advance, you'll learn how to transform 2D images into 3D printable solids, how to create multi-part prints that can be assembled without the use of fasteners or glue, and how to make sure your model, whether designed from scratch or assembled from preexisting geometry, is ready to be made real via your 3D printer. By the end of this book, you'll have the confidence to bring your design ideas to life by generating your own 3D print-ready models with SketchUp.